2019
DOI: 10.1051/e3sconf/201914002001
|View full text |Cite
|
Sign up to set email alerts
|

New high-speed system for controlling the parameters of a nuclear reactor in a nuclear power plant

Abstract: The necessity of modernizing current control systems for functional units of a nuclear power plant, as well as the development of new control systems with a high degree of reliability and speed, is substantiated. The advantages of using optical sensors and fiber-optic communication lines to solve these problems are noted. Cases for which it is necessary to develop new fiber-optic sensors for monitoring parameters, for example, the flow of coolant or feed water, are considered. In some of them, it is more exped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(4 citation statements)
references
References 50 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…In the compound CuFeS2 this value is small,  ~ 1 cm 2 V -1 s -1 , and almost independent of temperature in the interval measured. Such behavior is characteristic of a large-radius magnetic polaron (ferron) in antiferromagnetic, when the conduction electron creates a ferromagnetic region of radius around itself [25][26][27]. The results obtained are consistent with the results obtained on samples prepared using a conventional solid-phase reaction, as described earlier.13) The author noted that such samples give the Seebeck effect practically independent of temperatures above 100 K and show a large negative value at room temperature.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In the compound CuFeS2 this value is small,  ~ 1 cm 2 V -1 s -1 , and almost independent of temperature in the interval measured. Such behavior is characteristic of a large-radius magnetic polaron (ferron) in antiferromagnetic, when the conduction electron creates a ferromagnetic region of radius around itself [25][26][27]. The results obtained are consistent with the results obtained on samples prepared using a conventional solid-phase reaction, as described earlier.13) The author noted that such samples give the Seebeck effect practically independent of temperatures above 100 K and show a large negative value at room temperature.…”
Section: Resultssupporting
confidence: 85%
“…Therefore, taking these results and the small value of the electron concentration at low temperatures as the basis, we concluded that CuFeS2 belongs. to this class of compounds [19][20][21][22][23][24][25][26]. Similar investigations of CuFeTe, also reveal the existence of the power behaviour of the R(T), o(T) and n(T) values (figure 2).…”
Section: Resultsmentioning
confidence: 56%
“…( 9), (11), and ( 12). 4: while |y i − y 0 − χ i | > ϑ 1 > 0 and |ẏ i − ẏ0 | > ϑ 2 > 0, do 5: Compute the error e i,1 (21) using the solution to the dynamic systems (1) of agents i, k, k ∈ N i . 6: Approximate the nonlinear function Fi,1 based on estimators φ i,1,2 and ψ j,1,2 7: Calculate the derivative of y j using the TD (24).…”
Section: Algorithm 1 Finite-time Formation Control Algorithm With Pre...mentioning
confidence: 99%
“…Neural network-based, robust control, and event-triggered method are used respectively to address formation control problems for MASs with unknown nonlinear dynamics [8, 9, 17, 18], with system uncertainties and external disturbances [13, 14] and with switching topologies [15, 16]. The higher order systems arise in many engineering fields, including flexible robot manipulator [19], quadrotor with a variable degree of freedom [20], and nuclear power plant [21]. It can also be used to approximate partial differential equations by means of spatial discretization.…”
Section: Introductionmentioning
confidence: 99%